Internalisasi Tasawuf Al-Ghazali pada Masa Pandemi Covid-19 - Niam, M Khusnun; Hadi, Rahmad Tri (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This paper aims to describe, explain, and analyze by conducting an in-depth exploration of various literature that is in line with current topics, including those related to the covid-19 outbreak. Departing from the moral problems of humanity that are created from human responses to the current adult co-19 outbreak, thus forming panic and fear. The humanitarian crisis has become a fact that really happens in the field, many poor people who are starving, criminality, and of course related co-19 namely the rejection of the body is also related to the critical reasoning of a human and servant's religiosity. This research is a qualitative literature study, with a descriptive-analysis approach, which is an approach used to describe the data obtained and then analyzed and presented in the form of a description. In addition, the approach in this study uses the concept of the ‘ma'rifat’ and Sufism Al-Ghazali. The main sources of data in this study are covid-19 news and Al-Ghazali's work, for secondary sources in this study refer to articles, data, journals, and books that examine the concept of the ‘ma'rifat’ and the teachings of Sufism Al-Ghazali. The results of this study show that as a human being who is in this global pandemic, he should repent and forsake all sinful deeds. The existence of the coronavirus teaches humans to rethink worldly matters. For this reason, it is fitting for humans to know their God so that they can always be in a state of gratitude and remember their God in order to always be close and approached by their God.